ANALISIS KOMUNIKASI DAN INVOLVEMENT TERHADAP EMPLOYEE RELATIONS SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN - Puspita, Lia; Kasiyati, Sri Budi (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2021)
The policy of limiting social interaction (working from home) by the government since March 15, 2020, makes proper communication very important. Therefore, communication and involvement are important factors to improve employee relations and performance. The purpose of this study is to analyze the effect of communication and involvement on employee relations, the effect of communication and involvement on employee performance, the effect of employee relations on employee performance, and the effect of communication and involvement through employee relations on employee performance CV. Allsolutions, Surabaya. This study uses quantitative methods and the sample is 54 respondents. In collecting data, this study used a questionnaire, which was processed with IBM SPSS Statistics 22. The analysis technique used was path analysis. The results showed that Communication had a positive and significant effect on Employee Relations, Involvement had a positive, insignificant effect on Employee Relations, Communication and Involvement simultaneously had a positive and significant effect on employee relations, Communication and Involvement partially and simultaneously had a positive and insignificant effect on Employee performance, employee relations has a positive and significant effect on employee performance, and communication and involvement partially or simultaneously through employee relations has a positive and significant effect on employee performance. Employee relations has a significant influence to mediate the effect of Communication and Involvement on employee performance.